BENTUK RAGAM KONSULTATIF BAHASA INDONESIA DALAM KOMUNIKASI LISAN MAHASISWA PPL DENGAN GURU PAMONG DI SMA NEGERI 11 KOTA JAMBI (KAJIAN SOSIOLINGUISTIK) - Fahira Widiasari; Ade Rahima (Universitas Batanghari, 2025)
This research aims to describe and document forms of consultative Indonesian language forms in oral communication between PPL students and teachers at SMA Negeri 11 Jambi City. The study used in this research is sociolinguistic study. This research is a type of qualitative research using qualitative descriptive methods. These forms include three forms, including consultative forms of question sentences, consultative forms of explanatory sentences and consultative forms of greeting sentences. The main data in this research is oral communication containing a consultative variety of Indonesian which is used to be analyzed as research data. The data source was taken through recordings with different people using tapping data collection techniques at the school as the research site. Meanwhile, data analysis techniques were carried out using sociolinguistic theory. The results of this research are a description of the form of the consultative variety in Indonesian in the form of: (1) the form of a consultative variety of interrogative sentences which contains questions during communication, (2) the form of explanatory sentences of the consultative variety which contains the form of statements or explanations of questions when communicating, (3) the form of greeting sentences to start consultation or communication between tutor teachers and PPL students using a consultative variety that is not too standard and not too relaxed, prioritizing the results of oral communication between PPL students and teachers at SMA Negeri 11 Jambi city.